2013
DOI: 10.1182/blood-2013-05-500629
|View full text |Cite
|
Sign up to set email alerts
|

Targeting autophagy potentiates the apoptotic effect of histone deacetylase inhibitors in t(8;21) AML cells

Abstract: Key Points• In AML1-ETO-positive AML cells, HDAC inhibitors induce autophagy, which acts as a prosurvival signal to limit HDAC-induced cell death.• In contrast to the fusion oncoproteins PML-RARA and breakpoint cluster regionabelson, AML1-ETO is not degraded by either basal-or drug-induced autophagy.The role of autophagy during leukemia treatment is unclear. On the one hand, autophagy might be induced as a prosurvival response to therapy, thereby reducing treatment efficiency. On the other hand, autophagy may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 45 publications
1
93
0
Order By: Relevance
“…We and others have demonstrated that inhibition of autophagy leads to synergistic enhancement of the anticancer activity of HDAC inhibitors. 8,9,15,16,[19][20][21] These studies provided the foundation for the clinical evaluation of the autophagy inhibitor HCQ in combination with VOR as a potential novel therapy for advanced solid tumors. We selected 400 mg daily dosing for VOR in this study, which is frequently used for VOR administration.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have demonstrated that inhibition of autophagy leads to synergistic enhancement of the anticancer activity of HDAC inhibitors. 8,9,15,16,[19][20][21] These studies provided the foundation for the clinical evaluation of the autophagy inhibitor HCQ in combination with VOR as a potential novel therapy for advanced solid tumors. We selected 400 mg daily dosing for VOR in this study, which is frequently used for VOR administration.…”
Section: Discussionmentioning
confidence: 99%
“…13 For instance, in myeloid leukemia, autophagy induced by arsenic trioxide or all-trans retinoic acid contributes to cell death through the degradation of fusion oncoproteins such as promyelocytic leukemia-retinoic acid receptor alpha (PML-RARA) in acute promyelocytic leukemia cells or breakpoint cluster region-Abelson (BCR-ABL) in chronic myelocytic leukemia cells, whereas it does not mediate degradation of AML1-ETO (another oncoprotein involved in AML), and protects AML1-ETO AML cells from cell death induced by histone deacetylase inhibitors. [31][32][33][34] Thus, elucidating the role of autophagy in genetically defined AML subtypes is critical before exploiting autophagic properties as therapeutic approaches. 13 In addition to PML-RARA and BCR-ABL, our study shows that FLT3-ITD represents another leukemogenic protein targeted by autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…24 Notably, HDACIs also modulate autophagy. [25][26][27][28] Currently, the role of Bim in resistance to proteasome inhibitors such as bortezomib is largely unknown. Here we report that Bim is widely expressed in MM cells, and although basal Bim levels do not correlate with intrinsic bortezomib resistance, Bim downregulation confers adaptive bortezomib resistance in Bim hi MM cells.…”
Section: Introductionmentioning
confidence: 99%